Agarose gel implant with enhanced durability

By using BDDE as the cross -linked agent, combined with chemical cross -linking and self -concentrated physical cross -physical cross -leoning, prepare more persistent and better injected agarose gel implants, solving the existing implants in the body. Insufficient problem.

CN119367595APending Publication Date: 2025-01-28SUZHOU SUMEI MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310934001.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing agarose implants are insufficient in the body, resulting in frequent injections and inadequate injection process.

Method used

Using 1,4-butanol binary diodes (BDDE) as the linked agent of agar sugar, by controlling temperature control, combining chemical cross-linking and self-gathering physical cross-levit, preparing agar with longer body retention time Sugar gel implant.

Benefits of technology

It significantly improves the persistence and injection of agar sugar planting agents, making it retain it in the body for a longer time, and the injection process is more convenient and comfortable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367595A_ABST
    Figure CN119367595A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and particularly relates to a durability-enhanced agarose gel implant. The agarose gel is obtained by combining self-aggregation physical action and chemical crosslinking, and compared with agarose hydrogel formed only through the self-aggregation physical action, the agarose gel has better durability and can be kept in vivo for a long time. Meanwhile, the agarose gel disclosed by the invention has good injectability, so that the operation convenience of an injection person and the comfort of an injected person are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to an agarose gel implant with enhanced durability. Background Art

[0002] As we age, senescent cells accumulate and cause skin aging, resulting in reduced skin thickness, blocked proliferation, and changes in surface properties. Injecting biomaterials or synthetic biocompatible materials into the dermis or subcutaneous layer can achieve the purpose of reducing skin wrinkles or shaping through different mechanisms of action, thereby solving the problem of skin aging and restoring the natural healthy state. The selection of injection implant materials is a crucial link.

[0003] Agarose is a linear polysaccharide composed of β-D-galactose and 3,6-anhydro-α-L-galactose disaccharide repeating units connected by β-1,4 and α-1,3 glycosidic bonds. It is widely found in a variety of red algae, such as Gracilaria, Gelidium and Galleria. Agarose has the property of self-aggregating to form a gel with temperature changes. At high temperatures, it is in the form of a solution, and each small agarose chain is dispersed in water, but at low temperatures (<37°C), each chain is tightly entangled with each other to form a gel (LTA). Agarose has good physical and chemical properties and biocompatibility, does not contain toxic substances, does not cause hemolytic reactions, and can be phagocytosed and degraded and absorbed by macrophages. Therefore, high-purity agarose hydrogel can be used as a facial injection cosmetic agent to reduce wrinkles and improve skin sagging problems. In facial injections, the durability of the injection is very important. Implants with good durability can reduce the number of injections and injection pain, and have a more lasting filling effect. Therefore, it is of great significance to develop an injectable agarose implant with good durability.

[0004] The inventor unexpectedly discovered that by using 1,4-butanediol diglycidyl ether (BDDE) as a cross-linking agent for agarose and preparing it through temperature control, an agarose hydrogel with the combined effects of chemical cross-linking and self-aggregation physical cross-linking can be obtained. The cross-linked agarose gel not only retains the biocompatibility, non-immunogenicity, and non-irritation characteristics of agarose, but also has new characteristics. Compared with the agarose hydrogel formed by self-aggregation physical cross-linking, the agarose gel lasts longer in the body and has a more lasting effect. At the same time, the injectability of the gel has also been significantly improved, and the injection process is more convenient and comfortable. Summary of the invention

[0005] In view of the above technical problems, the purpose of the present invention is to provide a persistent agarose gel implant. The agarose gel implant prepared by the present invention can be retained for a longer time after being implanted in the skin. Specifically, it includes the following contents:

[0006] In a first aspect, the present invention provides a durable agarose gel implant, wherein the preparation method of the agarose gel implant comprises the following steps:

[0007] (1) Dissolve agarose in a buffer solution at 90-120°C to obtain a clear and transparent solution A;

[0008] (2) cooling the solution A in step (1) to 40-55° C., adding alkali to obtain solution B;

[0009] (3) allowing the solution B in step (2) to stand at 5-37° C. for 1-24 hours to obtain a hydrogel C;

[0010] (4) At 15-75° C., the hydrogel C described in step (3) is immersed in a buffer solution containing a chemical crosslinking agent for reaction for 5-48 hours, and an agarose gel implant is obtained after dialysis and homogenization.

[0011] Preferably, the step (1) is as follows: dissolving agarose in a buffer solution at 90-120° C., stirring and refluxing for 20-60 min to obtain a clear and transparent solution A.

[0012] Preferably, the temperature in step (1) is 105°C.

[0013] Preferably, the temperature in step (2) is 40-50°C.

[0014] Preferably, the temperature in step (3) is 25°C.

[0015] Preferably, the pH of the buffer solution in step (1) is 6.5 to 7.5.

[0016] Preferably, the pH of the buffer solution in step (1) is 7.4.

[0017] Preferably, the buffer solution is a phosphate buffer solution.

[0018] Preferably, the phosphate buffer solution is a sodium dihydrogen phosphate solution, a disodium hydrogen phosphate solution or a mixed solution of the two.

[0019] Preferably, the base is selected from any one of sodium carbonate, sodium bicarbonate and sodium hydroxide.

[0020] Preferably, the base is sodium hydroxide.

[0021] Preferably, the mass percentage concentration of the sodium hydroxide is 0.1%-1%.

[0022] Preferably, the mass percentage concentration of the sodium hydroxide is 0.5%-0.6%.

[0023] The cross-linking agent is an epoxide cross-linking agent.

[0024] Preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether.

[0025] Preferably, the mass percentage concentration of the 1,4-butanediol diglycidyl ether is 0.5%-4.5%.

[0026] Preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether with a mass percentage concentration of 1%-2.5%.

[0027] Preferably, the content of agarose is 10-25 mg / mL.

[0028] The present invention has the following beneficial effects: compared with agarose gel (LTA) formed by pure self-aggregation physical cross-linking, the agarose gel implant (LTA+BDDE) of the present invention has the following characteristics: ① The present invention successfully prepares an agarose implant with a longer in vivo retention time by controlling the use of a cross-linking agent and the cross-linking temperature, thereby enhancing its lasting performance and making the LTA+BDDE gel a longer-lasting agarose implant; ② The agarose gel implant (LTA+BDDE) of the present invention has lower mechanical strength and viscosity, thereby improving its injectability and making the injection process more convenient and uniform; ③ These characteristics give the agarose implant a broader application potential in the field of dermatology, and provide a reliable solution for improving problems such as wrinkles and skin sagging. Therefore, the present invention opens up a new path for the research and development of agarose implants and has important clinical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Fourier transform infrared spectra of different agarose hydrogels;

[0030] Figure 2 Acid degradation rate diagram of different agarose hydrogels;

[0031] Figure 3 SEM images of different agarose hydrogels.

[0032] Figure 4 Injection force diagram of different agarose hydrogels;

[0033] Figure 5 Storage modulus and loss modulus plots of different agarose hydrogels;

[0034] Figure 6 Shear viscosity plots of different agarose hydrogels. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with embodiments and drawings, but the present invention is not limited by the following embodiments.

[0036] Example 1 Preparation of LTA+BDDE Hydrogel

[0037] Preparation of 1.1% LTA+BDDE hydrogel

[0038] Dissolve 0.1g agarose in 10mL PBS buffer solution at 105°C, stir and reflux for 30min, then cool to 45°C, add 0.05g NaOH and stir for 3min. Let the above uniform solution stand at 25°C for 5h to obtain a self-aggregated agarose hydrogel. At 45°C, soak the obtained hydrogel in a PBS buffer solution containing 2% BDDE, react for 24h, then dialyze in PBS buffer, and the obtained gel is homogenized to obtain a 10mg / mL (1%) agarose hydrogel LTA+BDDE with a self-aggregated physical effect and chemical cross-linking.

[0039] Preparation of 2.2.5% LTA+BDDE hydrogel

[0040] Dissolve 0.25g agarose in 10mL PBS buffer solution at 105℃, stir and reflux for 30min, then cool to 50℃, add 0.05g NaOH and stir for 4min. Let the above uniform solution stand at 25℃ for 5h to obtain self-aggregated agarose hydrogel. At 45℃, soak the obtained hydrogel in PBS buffer solution containing 2% BDDE, react for 24h, then dialyze in PBS buffer, and the obtained gel is homogenized to obtain agarose hydrogel LTA+BDDE with a content of 25mg / mL (2.5%), which is a self-aggregated physical effect and chemical cross-linking.

[0041] 3. Preparation of LTA Hydrogel

[0042] 0.1 g of agarose was dissolved in 10 mL of PBS buffer solution at 100° C., stirred and refluxed for 30 min, and then the solution was allowed to react at 37° C. for 24 h. The resulting gel was homogenized to obtain an LTA hydrogel with a content of 10 mg / mL (1%).

[0043] 0.25 g agarose was dissolved in 10 mL PBS buffer solution at 110° C., stirred and refluxed for 35 min, and then the solution was allowed to react at 37° C. for 24 h. The obtained gel was homogenized to obtain LTA hydrogel with a content of 25 mg / mL (2.5%).

[0044] 4. Preparation of LTA-BDDE Hydrogel

[0045] 0.1 g agarose was dissolved in 10 mL PBS buffer solution at 100°C, stirred and refluxed for 30 min, then cooled to 43°C, 0.05 g NaOH and 0.15 mL BDDE were added, and stirred for 3 min. The above homogeneous solution was allowed to react at 25°C for 24 h, then dialyzed in PBS buffer, and the obtained gel was homogenized to obtain LTA-BDDE hydrogel with an agarose content of 10 mg / mL (1%).

[0046] 0.25 g agarose was dissolved in 10 mL PBS buffer solution at 110°C, stirred and refluxed for 35 min, then cooled to 50°C, 0.05 g NaOH and 0.15 mL BDDE were added, and stirred for 5 min. The above homogenous solution was allowed to react at 25°C for 24 h, then dialyzed in PBS buffer, and the obtained gel was homogenized to obtain LTA-BDDE hydrogel with an agarose content of 25 mg / mL (2.5%).

[0047] Example 2 Preparation of Agarose Hydrogel Freeze-Dried Sponge

[0048] The 1% LTA+BDDE, 2.5% LTA+BDDE, 1% LTA, 2.5% LTA, 1% LTA-BDDE and 2.5% LTA-BDDE unhomogenized hydrogels prepared in Example 1 were pre-frozen at low temperature for 14 hours and vacuum freeze-dried for 24 hours to form agarose hydrogel sponges.

[0049] Example 3 Infrared Characterization of LTA+BDDE Hydrogel

[0050] The Fourier transform infrared spectra of the freeze-dried samples of prepared agarose hydrogel (1% LTA+BDDE, 2.5% LTA+BDDE) are shown in Figure 2. Figure 1 As shown. 1000-1200cm -1 It is the CO stretching vibration peak, 1161cm after BDDE cross-linking -1 The peak at 2700-3000cm disappears because the epoxy bond of BDDE reacts with the primary hydroxyl group of agarose to form an ether, and the CO stretching vibration peak of the primary hydroxyl group (-CH2OH) becomes the CO stretching vibration peak of the ether bond (COC). -1 It is the CH stretching vibration peak, which is at 2900cm after BDDE cross-linking. -1 There is a split peak near the BDDE, which is because many new CH bonds are introduced after cross-linking with BDDE. These results show that BDDE successfully cross-links agarose.

[0051] Example 4 In vitro degradation test of LTA+BDDE hydrogel

[0052] Test samples: various agarose hydrogel freeze-dried sponges prepared in Example 2

[0053] The six freeze-dried sponges of 1% LTA+BDDE, 1% LTA, 1% LTA-BDDE, 2.5% LTA+BDDE, 2.5% LTA and 2.5% LTA-BDDE in Example 2 were weighed and placed in a centrifuge tube to reach swelling equilibrium in PBS buffer, and then immersed in PBS buffer containing hydrochloric acid at 37°C to characterize the degradation behavior of the hydrogel. Samples were taken at regular intervals, the supernatant was removed after centrifugation, and the precipitate was freeze-dried and weighed (W t The acid degradation rate is calculated according to the following formula: Weight loss (%) = (W0-W t ) / W0×100%.

[0054] The results of in vitro degradation behavior are shown in Figure 2 The results showed that at 72 hours, 1% LTA degraded by 91%, 1% LTA-BDDE degraded by 92%, while 1% LTA+BDDE described in the present application degraded by only 66%; 2.5% LTA degraded by 32%, 2.5% LTA-BDDE degraded by 28%, while 2.5% LTA+BDDE described in the present application degraded by only 15%. Compared with LTA and LTA-BDDE, the LTA+BDDE hydrogel described in the present application showed higher resistance to degradation and better durability, and is a longer-lasting agarose implant.

[0055] Example 5 Effect of BDDE Dosage on Preparation and Properties of Agarose Hydrogel

[0056] Dissolve 0.1g agarose in 10mL PBS buffer solution at 105°C, stir and reflux for 30min, then cool to 45°C, add 0.05g NaOH and stir for 3min. Let the above uniform solution stand at 25°C for 5h to obtain a self-aggregated agarose hydrogel. Soak the obtained hydrogel in PBS buffer solutions containing 0%, 0.5%, 1%, 1.5%, 2%, 2.5% and 3% BDDE, respectively, and react for 24h to obtain a reaction product.

[0057] When the BDDE dosage is 0%, 0.5%, 1%, 1.5%, 2%, 2.5% and 3% BDDE, the obtained product is still a gel, but its degradation resistance is different. The acid degradation results are shown in Table 1 below.

[0058] Table 1 Acid degradation results of agarose hydrogel under different BDDE dosage conditions

[0059] BDDE dosage% 0 0.5 1 1.5 2 2.5 3 72h degradation percentage % 91 90.2 90 74 66.5 66 66

[0060] The experimental results show that when using BDDE, a higher dosage can improve the anti-degradation performance of agarose gel; when the BDDE dosage reaches 2%, the prepared gel shows the minimum degradation rate. Therefore, in order to ensure a more lasting effect in the body, a sufficient amount of BDDE needs to be used to prepare the hydrogel.

[0061] Example 6 Effect of Temperature on Preparation and Properties of Agarose Hydrogel

[0062] Dissolve 0.1g agarose in 10mL PBS buffer solution at 105℃, stir and reflux for 30min, then cool to 45℃, add 0.05g NaOH and stir for 3min. Let the above uniform solution stand at 25℃ for 5h to obtain self-aggregated agarose hydrogel. Soak the obtained hydrogel in PBS buffer solution containing 2% BDDE for 24h, and the reaction temperatures are 15℃, 25℃, 35℃, 45℃, 55℃, 65℃ and 75℃ respectively to obtain the reaction product.

[0063] When the temperature is 15°C, 25°C, 35°C, 45°C, 55°C, 65°C and 75°C, the obtained product is still a gel, but its degradation resistance is different. The acid degradation results are shown in Table 2 below.

[0064] Table 2 Acid degradation results of agarose hydrogel under different temperature conditions

[0065] temperature 15℃ 25℃ 35℃ 45℃ 55℃ 65℃ 75℃ 72h degradation percentage % 89 75 70 66 67 90 95

[0066] The experimental results show that the soaking temperature during the preparation of the gel has a significant effect on its anti-degradation performance. When the reaction temperature is set at 45°C and 55°C, the prepared gel exhibits the smallest degradation rate. Therefore, controlling the soaking temperature is crucial in achieving a longer-lasting effect.

[0067] Example 7 Scanning electron microscopy (SEM) characterization of LTA+BDDE hydrogel

[0068] The LTA+BDDE and LTA sponge samples prepared in Example 2 were fixed on the sample stage of a scanning electron microscope, sprayed with gold for 25 seconds, and then the sample morphology was detected using a scanning electron microscope at an operating voltage of 5.0 kV.

[0069] Scanning electron microscopy (SEM) results show Figure 3 The results showed that the meshes of LTA and LTA+BDDE were dense and uniform, with a tight structure; chemical cross-linking did not change the mesh structure of LTA.

[0070] Example 8 Injectability test of LTA+BDDE hydrogel

[0071] Test samples: 1% LTA+BDDE, 1% LTA, 2.5% LTA+BDDE and 2.5% LTA hydrogels prepared in Example 1.

[0072] This test uses a texture analyzer to test the needleability of the sample. During the test, the injection needle is installed and the core rod is pushed at a constant speed. The sample in the syringe is pushed out through the needle to obtain the extrusion force curve. The extrusion force curve shows the change of the extrusion force during the sample extrusion process. The smaller the extrusion force, the easier the sample is to be extruded and the better the injectability.

[0073] The results of the injection test are as follows Figure 4 As shown. The results show that the pushing force curve of LTA gel has a certain drop, especially the high concentration of 2.5% LTA, indicating that the sample is unevenly dispersed, affecting the hand suitability during injection. The present application changes this result by chemical cross-linking with BDDE. The pushing force of the prepared LTA+BDDE gel is more uniform and gentle during injection, and the pushing force is reduced to a certain extent, making the injection of agarose implants easier and improving the injectability of the implants.

[0074] according to Figure 4 The results of the injectability test in the results show that the pushing force curve of the LTA gel has certain fluctuations, especially at a high concentration of 2.5% LTA, indicating that the uneven dispersion of the sample may affect the handiness during injection. However, the present application changes this situation by chemically cross-linking BDDE, and the prepared LTA+BDDE gel presents a more uniform and gentle pushing force curve during injection. In addition, the magnitude of the pushing force is also significantly reduced, making the agarose implant easier to inject, thereby improving its injectability.

[0075] Example 9 Rheological properties test of LTA+BDDE hydrogel

[0076] The LTA+BDDE and LTA gels with uniform thickness of 1 cm×1 cm×2 mm prepared according to Example 1 were then placed on the sample stage of the rheometer, the shear strain of the rheometer was fixed, and the storage modulus G' (Pa) and loss modulus G" (Pa) of the gels were tested as a function of angular frequency.

[0077] The rheological mechanical properties test results of LTA+BDDE and LTA gels are shown in Figure 5 When the angular frequency is 10.7 rad / s, the storage modulus of 1% LTA reaches 20889 Pa; the storage modulus of 1% LTA+BDDE reaches 7389.9 Pa; the storage modulus of 2.5% LTA reaches 92280 Pa; the storage modulus of 2.5% LTA+BDDE reaches 31612 Pa; compared with LTA, the storage modulus and loss modulus of LTA+BDDE prepared in this application are significantly reduced, which is conducive to the injection of agarose.

[0078] Example 10 Shear viscosity test of LTA+BDDE hydrogel

[0079] The LTA+BDDE and LTA gels of uniform thickness of 1 cm×1 cm×2 mm prepared in Example 1 were placed on the sample stage of the rheometer and the rheometer was used to adjust the shear rate from 0.01 s -1 ~1 000s -1 The peristaltic scanning was performed under the condition of , and the shear viscosity of different gels was obtained. The test results are shown in Figure 6 shown.

[0080] The results showed that as the shear rate increased, the viscosity of LTA+BDDE and LTA gel decreased, indicating that agarose gel has a shear thinning effect. Compared with LTA, the shear viscosity of LTA+BDDE prepared in this application is smaller, LTA+BDDE exhibits a more significant shear thinning effect, and the force required for injection is smaller.

[0081] In summary, the present invention uses 1,4-butanediol diglycidyl ether (BDDE) as a cross-linking agent for agarose, and improves the performance of LTA hydrogel through chemical cross-linking. LTA+BDDE hydrogel shows significant advantages in terms of anti-degradation and can remain in the body for a longer time. Therefore, it can be used as a durable agarose implant for applications such as skin filling. In addition, LTA+BDDE hydrogel has good injectability, and the injection process is smoother and more comfortable. The discovery of this technology provides new ideas and methods for the research and development of agarose implants, and has broad application prospects and market potential.

[0082] The above description is only the details of individual exemplary implementation cases of the present invention. For those skilled in the art, the present invention may have various modifications and changes according to specific preparation conditions during actual application, and is not intended to limit the present invention. Anything within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A persistent agarose gel implant, characterized in that: The preparation method of the agarose gel implant comprises the following steps: (1) Dissolve agarose in a buffer solution at 90-120°C to obtain a clear and transparent solution A; (2) cooling the solution A in step (1) to 40-55° C., adding alkali to obtain solution B; (3) allowing the solution B in step (2) to stand at 5-37° C. for 1-24 hours to obtain a hydrogel C; (4) At 15-75° C., the hydrogel C described in step (3) is immersed in a buffer solution containing a chemical crosslinking agent for reaction for 5-48 hours, and an agarose gel implant is obtained after dialysis and homogenization.

2. The agarose gel implant according to claim 1, characterized in that The pH of the buffer solution in step (1) is 6.5 to 7.

5.

3. The agarose gel implant according to claim 2, characterized in that: The pH of the buffer solution in step (1) is 7.

4.

4. The agarose gel implant according to claim 1, characterized in that: The buffer solution is a phosphate buffer solution.

5. The agarose gel implant according to claim 1, characterized in that: The alkali is selected from any one of sodium carbonate, sodium bicarbonate and sodium hydroxide.

6. The agarose gel implant according to claim 5, characterized in that: The alkali is sodium hydroxide, and the mass percentage concentration of the sodium hydroxide is 0.1%-1%.

7. The agarose gel implant according to claim 6, characterized in that: The mass percentage concentration of the sodium hydroxide is 0.5%-0.6%.

8. The agarose gel implant according to claim 1, characterized in that: The cross-linking agent is 1,4-butanediol diglycidyl ether, and the mass percentage concentration of the 1,4-butanediol diglycidyl ether is 0.5%-4.5%.

9. The agarose gel implant according to claim 8, characterized in that: The cross-linking agent is 1,4-butanediol diglycidyl ether with a mass percentage concentration of 1%-2.5%.

10. The agarose gel implant according to claim 1, characterized in that: The content of the agarose is 10-25 mg / mL.

Citation Information

Cited By

  • Composite implant containing agarose with different molecular weights as well as preparation method and application of composite implant

    CN120154754A